2019
DOI: 10.1111/ijpo.12587
|View full text |Cite
|
Sign up to set email alerts
|

An examination of sex differences in associations between cord blood adipokines and childhood adiposity

Abstract: Summary Background Though the physiological roles of adipokines in metabolism, insulin resistance and satiety are clear, literature regarding associations between cord blood adipokine levels and childhood adiposity is equivocal. Objectives To determine whether cord blood levels of leptin and adiponectin are associated with adiposity in children 2 to 5 years of age, and whether such associations are modified by sex. Methods Leptin and adiponectin levels were measured in cord blood and anthropometric measures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
3
6
1
Order By: Relevance
“…Ghrelin levels increased significantly during the first 6 months of life, which is in line with a study from birth until 3 months [31], while PYY and leptin levels decreased. Our results complement current knowledge as other studies used cord blood to investigate leptin at birth [16,17], a single measurement of ghrelin, PYY and leptin at 4 months [24] or a single measurement of ghrelin and leptin between 11 days and 22 months [23]. One study investigated leptin in multiple measurements until age 6 months, but only in a small group [32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ghrelin levels increased significantly during the first 6 months of life, which is in line with a study from birth until 3 months [31], while PYY and leptin levels decreased. Our results complement current knowledge as other studies used cord blood to investigate leptin at birth [16,17], a single measurement of ghrelin, PYY and leptin at 4 months [24] or a single measurement of ghrelin and leptin between 11 days and 22 months [23]. One study investigated leptin in multiple measurements until age 6 months, but only in a small group [32].…”
Section: Discussionsupporting
confidence: 82%
“…These first 6 months after birth are considered a critical window for adiposity programming [9,10], ARH trajectories might be of importance in unraveling this early adiposity programming. ARH have been associated with later growth and adiposity, but most studies used cord blood [13][14][15][16][17][18] or newborn blood spots [19,20] to investigate ARH at birth or in specific groups (such as infants born premature or small-for-gestational age) [21,22]. However, data on ghrelin, PYY and leptin trajectories during early life in healthy term-born infants are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, we found that the participants’ BMI had an impact on leptin concentration emphasizing good data quality as the relationship between leptin and BMI is well-known [ 7 ]. Good data quality is also supported by the well-known sex-dependent differences of adipokines as well as the adiponectin/leptin ratio in men and women, which is also observed in our trial [ 10 , 36 , 37 , 38 , 39 , 40 ]. Interestingly, the results of our and other studies emphasize not only the previously known fundamental difference in adipokine levels in men and women, but also a supposed sex-difference in alterability by diet or specific nutritional components [ 41 ].…”
Section: Discussionsupporting
confidence: 80%
“…Sex-dependent differences in adipokine levels are known for a long time [23][24][25], and the results of our trial also show sex-dependent differences leading to the performed subgroup analyses. The results of our and other studies emphasize not only the previously known fundamental difference of adipokine levels in males and females, but also a supposed sex-difference in alterability by diet or speci c nutritional components [26].…”
Section: Discussionsupporting
confidence: 63%